The Role of Librarians in the Implementation of Knowledge Management in IPDN Libraries - Delis Sri Maryati; Iim Wasliman; Achmad Mudrikah; R. Supyan Sauri (CV. AFDIFAL MAJU BERKAH, 2021)
This research describe about the role of librarians in the implementation of knowledge management in IPDN library. The general purpose of this study was to determine the role of librarians in the implementation of knowledge management in the IPDN Library. This research uses qualitative research with descriptive method. As a result, librarians have implemented knowledge management by means of knowledge identification, knowledge acquisition, knowledge development, knowledge sharing management and knowledge storage.